The Triple Burden: A Case of Very Severe Chronic Obstructive Pulmonary Disease at the Intersection of Tobacco Smoke, Occupational Dust, and Post-Tuberculosis Sequelae - Siti Ulfa Furiani; Diana Rahmaniar (International Medical Journal Corp. Ltd, 2025)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a heterogeneous condition with multiple etiologies. The confluence of tobacco smoke, occupational hazards, and post-tuberculosis lung disease (PTLD) presents a significant diagnostic and therapeutic challenge, often resulting in a severe clinical phenotype. Case Illustration: We present the case of a 56-year-old male construction worker with a significant smoking history and a history of cured pulmonary tuberculosis, who presented with an acute exacerbation of dyspnea. Physical examination revealed signs of severe airflow obstruction, including tachypnea, pursed-lip breathing, and a barrel chest. Diagnostic workup, including a Pulmonary Update in Medical Assessment (PUMA) score of 8 and a COPD Assessment Test (CAT) score of 36, indicated a high disease burden. Post-bronchodilator spirometry confirmed very severe, irreversible airflow obstruction (Forced Expiratory Volume in 1 second [FEV1] 23% predicted; FEV1/Forced Vital Capacity [FVC] ratio 0.337). Chest radiography demonstrated emphysematous changes superimposed on fibrotic sequelae from prior tuberculosis. Discussion: The patient's profound respiratory impairment is attributed to a